Strategi Pengembangan Ekowisata Berbasis Ekonomi Lokal di Kawasan Geopark Kabupaten Natuna - Rommy Rommy; Darmanto Darmanto; Rudi Subiyakto (Jurnal Pendidikan Indonesia, 2025)
Tourism development trends continue to be developed to encourage and increase local economic growth. The increase in incoming tourists has a positive impact on a region on the foreign exchange received and can increase growth in the hotel, restaurant, and other businesses in the tourism sector. With the recognition of the Natuna area as a National Geopark, it is hoped that it will be able to create real benefits in preserving nature, empowering local communities and improving the economy of local communities in Natuna Regency. However, based on available data, the number of tourists visiting the Geopark area has not shown a large increase and influence in improving the economy of the Natuna community, especially in the Geopark area. The purpose of the research is to analyze the implementation of tourism and tourism development strategies in the Natuna Regency Geopark Area towards improving the economy of the surrounding community. The researcher uses the theory put forward by (Cooper et al., 1993) about tourism development which includes Attractions, Amenities, Accessbility and Ancillary Service. The research uses a qualitative method with a strategy concept including the input stage, the TWOS matrix matching stage, and the decision stage using QSPM. The results of the study show that the Development of Local Economy-Based Ecotourism in the Natuna Regency Geopark Area has not been carried out optimally. The best strategy resulting from the QSPM matrix is to create a stronger and more appropriate narrative and branding regarding Ecotourism and Geoparks both to prospective tourists and other stakeholders and also by exploring potential new attractions and markets.